La pedagogía Waldorf en Educación Inicial - Jiménez Vera, Karla Lizet (2017)
The present investigation had as reference the study of the Waldorf Pedagogy in Initial Education of the Educational Unit "Luis Enrique Raza Bolaños", located in the canton Quito, province of Pichincha in the year 2016-2017, the same one had the objective to determine the incidence Of this pedagogy in the infantile education, through the application of investigative techniques to determine the degree of knowledge of the actors that form parts of the establishment; In addition a diagnosis of the results obtained was made through the elaboration of conclusions and recommendations; To fulfill this task, we investigated and compiled information and articles inherent to the mentioned methodology to analyze the origins, main characteristics and applications. The research is based on a qualitative-quantitative approach, followed by interviews with teachers and managers of the school, surveys of parents and finally records of observation applied to boys and girls subject to the study. With all the information and data obtained it is expected to visualize the Waldorf pedagogy in a clear, comprehensible and precise way to apply it to children of the initial level. This research belongs to the Anthroposophical current that postulates the division of three parts: the intellectual legacy, the artistic legacy and the disciplinary legacy. Within the aulic project will work with eurythmy since it works with movement and sound; That is, important elements for initial education, which considers that growth is individual by nature and makes different individuals taking into account qualities such as adaptability, creativity and common sense. The impact of this pedagogy on education was quite positive since the main difference is in seeing the development of the child in a different, integral way; Of this new vision, is derived a way of educating it according to the stages through which it is happening in infant.